A study on strategic management, competition, and cost effective: Analyzing their combined impact on performance in malaysia’s grade 1 construction industry - Wan Saiful Hafez Amran; Gazi Md Nurul Islam; Mustafa Dakian (Journal of Management and Science, 2025)
The aim/objectives of study is to establish the effects of management strategy, competition and cost on the performance of the GRADE 1 contractors in the construction Industry of Malaysia. This research examines Strategic Management, Competition and Cost Management as the three independent variables in the context of Malaysia’s GRADE 1 contractors in the industry to examine their impact and contribution on the performance as dependent variables and sustainability in Malaysia’s construction industry. The research design is applied the cross-sectional method with focusing mainly on the constructions industry, The target population of this research is the G1 construction industry in Malaysia and data was collected purposively from 1,500 members of the Malaysian Malay Contractors Association (PKMM). There are 165 respondents (33.0%) from 500 members as a responsive rate involved. The quantitative technique was adopted for this study and Multiple Linear Regression as well as Spearman’s correlation tests were conducted to assess the correlation between the independent variables and the dependent variable, performance of GRADE 1 construction firms. The finding of study shows that performance is positively influenced by both Strategic Management and Cost, where Cost is the leading factor. While there is a strong positive relationship between Competition and performance, its co-efficient is less than other factors, making it clear that in this particular context the aptitude of Competition is considerably low. Consequently, the implications of study is findings affirm that planning and efficient Cost Management are essential factors for enhancing performance in the GRADE 1 construction sector. As such, future studies should cover a longer period and cover other construction grades and regions. The contributions of study that this research expands the current theoretical understanding of strategic and operation factors affecting GRADE 1 construction firms in Malaysia, and presents managerial and policy implications for the construction fraternity.